2004
DOI: 10.7326/0003-4819-141-3-200408030-00009
|View full text |Cite
|
Sign up to set email alerts
|

Compensation and Advancement of Women in Academic Medicine: Is There Equity?

Abstract: Female medical school faculty neither advance as rapidly nor are compensated as well as professionally similar male colleagues. Deficits for female physicians are greater than those for nonphysician female faculty, and for both physicians and nonphysicians, women's deficits are greater for faculty with more seniority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(233 citation statements)
references
References 28 publications
4
225
1
3
Order By: Relevance
“…Advancement is usually slower, and salaries are often lower for women than for men. 2,[20][21][22][23][24] Not surprisingly in light of these findings, the departure rates from academic medical faculties are greater for women than for men. 25 The extent to which women participate in service and teaching relative to research activities may affect their advancement, particularly in research-intensive schools.…”
Section: The Trajectory Of Advancement For Women In Academic Medicinementioning
confidence: 99%
“…Advancement is usually slower, and salaries are often lower for women than for men. 2,[20][21][22][23][24] Not surprisingly in light of these findings, the departure rates from academic medical faculties are greater for women than for men. 25 The extent to which women participate in service and teaching relative to research activities may affect their advancement, particularly in research-intensive schools.…”
Section: The Trajectory Of Advancement For Women In Academic Medicinementioning
confidence: 99%
“…However, studies have documented significant gender inequality in the field of medicine. Female physicians are less likely to be promoted or to serve in leadership positions than comparably credentialed men, and significant gender salary gap exists even after adjustment for factors such as seniority, specialty, hours worked, and academic productivity (Tesch et al 1995;Wright et al 2003;Ash et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…They found that in the subset of men and women who explicitly aspired to become CEO and who did not have children, women lagged behind men from day one. Such findings were also described by Ash et al (2004) who conducted a large scale comparison of almost 2,000 medical school faculty members in 24 medical schools in the United States. Their work showed a rank and salary disparity between male and female faculty.…”
Section: Discussionmentioning
confidence: 80%